Dampak Haptic Information terhadap Product Perception, Consumer Trust, dan Online Purchase Intention pada Media Sosial Instagram (Studi pada Produk Sounds Husky - R. Khairizza Mohammad; Gunawan, Sri (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
This study aims to examine the impact of differences in haptic description and style description on haptic information and product perception in their effects on consumer trust, and online purchase intentions. Experimental design with between subjects was used to test the 2 x 1 factorial design research model. Where, two groups would get random stimuli between haptic description and style description with a total sample of 100 people. The findings in this study are that haptic description has a higher influence on haptic information and product perception compared to style description. Furthermore, haptic information has a positive effect on product perception and consumer trust, but does not have an influence on online purchase intention. The findings in this study suggest that apparel businesses in Instagram are expected to be able to provide product photo quality and more detailed haptic descriptions to create better product perception in the minds of consumers. Furthermore, the sentence written on the caption is also expected to be made to be more persuasive, so that the three things suggested can increase online purchase intention.